ANALISA KOEFISIEN UJUK KERJA MESIN PENDINGIN (CHILLER) UNIT 1 PADA POWER HOUSE - Julianto Sinaga; Yovan Witanto; Agus Nuramal (UNIB Press, 2022)
Each refrigerant has different characteristic properties which affect the refrigeration effect and the resulting coefficient of performance (COP). A refrigeration machine that works by cooling water is called a refrigeration machine chillers. Chiller is an air conditioner with no cooling system direct. In this indirect cooling system, the refrigeration engine does not instantly cools the air in every room. Refrigeration machine cools water demin first, then this cold demin water is used for cool the air in the room. Cold demin water as cooling medium to reduce the temperature of a wide room at power house (PH) PLTA Musi. The method used in working on this practical work report is:by making observations or observations in the field, conducting interviews (interview) with supervisors and practical work supervisors regarding theoretical data (specification data). In this study, the Cooling Performance Coefficient (COP) was analyzed On Power House (PH) PT PLN (PERSERO) UL PLTA Musi The results of this study get the conclusion, namely: The coefficient of performance (COP) on the machine chiller unit 1 in Power House PLTA Musi by 4.22 is smaller than specification coefficient. This indicates that the cooling system is working properly optimal.